Penerapan Matematika Realistik Untuk Meningkatkan Pemahaman Terhadap Materi Penjumlahan dan Pengurangan Pecahan - Ridha Aini Kamilah (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This research is based on the emergence of the problem of students' low understanding of the concept of Addition and Subtraction of Fractions. The approach chosen is a realistic mathematical approach. The research method used is classroom action research (CAR). This research consists of three cycles. The instruments used are learning instruments (RPP and LKS) and data collection instruments consisting of test instruments (formative tests and sub summative tests) and non-test instruments (observation sheets, student journals, questionnaires and interviews). This research was conducted in class VI SD Negeri 016404 Silau Jawa. The results showed an increase in understanding and positive responses of sixth grade students. this can be seen from the results of the formative test which showed a significant increase between cycles. Students also gave a positive response to this learning. This can be seen from their enthusiastic attitude in participating in learning with a realistic mathematics approach. Students who initially lacked attention, gradually turned into concentration, because they felt happy about this realistic mathematical approach. In group work, students also seemed enthusiastic in discussing with their friends. This indicates that there is a positive response from students towards a realistic mathematics approach. Keywords: realistic mathematics; summation; subtraction Abstrak: Penelitian ini bertitik tolak dari munculnya permasalahan rendahnya pemahaman siswa terhadap konsep Penjumlahan dan Pengurangan Pecahan. Pendekatan yang dipilih adalah pendekatan matematika realistik. Metode penelitian yang digunakan adalah penelitian tindakan kelas (PTK). Penelitian ini terdiri atas tiga siklus. Instrumen yang digunakan adalah instrumen pembelajaran (RPP dan LKS) dan instrumen pengumpul data yang terdiri dari instrumen tes (tes formatif dan tes sub sumatif) dan instrumen non tes (lembar observasi, jurnal siswa, angket dan wawancara). Penelitian ini dilaksanakan di kelas VI SD Negeri 016404 Silau Jawa. Hasil penelitian menunjukkan adanya peningkatan pemahaman dan respon positif siswa kelas VI. hal ini dapat dilihat dari hasil tes formatif yang menunjukkan peningkatan yang signifikan antar siklus. Siswa juga memberikan respon positif terhadap pembelajaran ini. Hal ini terlihat dari sikap mereka yang antusias dalam mengikuti pembelajaran dengan pendekatan matematika realistik. Siswa yang semula kurang perhatian, lambat laun berubah menjadi konsentrasi, karena mereka merasa senang terhadap pendekatan matematika realistik ini. Dalam bekerja kelompok siswa juga tampak antusias berdiskusi dengan temannya. Hal ini mengindikasikan adaya respon positif dari siswa terhadap pendekatan matematika realistik. Kata kunci: matematika realistic; penjumlahan; pengurangan